2017
DOI: 10.1080/14783363.2017.1283211
|View full text |Cite
|
Sign up to set email alerts
|

The effect of TQM on organisational performance: empirical evidence from the textile sector of a developing country using SEM

Abstract: Total Quality Management (TQM) is a widely used management philosophy across many sectors. Organisations implement TQM in order to gain competitive advantage in terms of quality, productivity, customer satisfaction, and profitability. However, the literature seems inconclusive about the positive effect of TQM on organisational performance. Several studies argue that the effect of TQM practices on organisational performance need to be evaluated in different social, cultural, and economic settings. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
195
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(220 citation statements)
references
References 65 publications
20
195
1
4
Order By: Relevance
“…Our firm export has fully met our expectation. Source: Shafiq et al (2017); Boso et al (2012); Shoham et al (2008) …”
Section: Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our firm export has fully met our expectation. Source: Shafiq et al (2017); Boso et al (2012); Shoham et al (2008) …”
Section: Satisfactionmentioning
confidence: 99%
“…The total quality management in this study contains five dimensions, where the leadership, strategy, people, resources, and process contained 6, 6, 6, 5 and 7 respectively (Shafiq et al, 2017).…”
Section: Measures Of Variablesmentioning
confidence: 99%
“…The operationalization of total quality management is not thus far developed, subsequently, researchers operationalized the TQM on the theme of TQM practices, some of studies operationalized base on TQM models such as Malcolm Baldrige National Quality Award (MBNQA) and European Foundation for Quality Management (EFQM) (Jafari, 2013). Moreover, a most famous model which got more intention is a European Foundation for Quality Management (EFQM), this is more applicable in the valuation of the firm performance (M. Shafiq et al, 2017). Nevertheless, some of the researchers found a positive connection between total quality management and export performance and further they suggested that TQM can be an influential resource for SME export performance, especially in context of Pakistan (Abeykoon & de Alwis, 2016;Lages et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The TQM in this study contains five dimensions including leadership, strategy, people, resources, and process contained with numbers of 6, 6, 6,5 and 7, respectively (Muhammad Shafiq et al, 2017). In addition, the modified version of export performance (EXPERF) scale with 9 items (Shoham et al, 2008) was adapted.…”
Section: Measures Of Variablesmentioning
confidence: 99%